Aeroelastic characteristics of linear and nonlinear piezo-aeroelastic energy harvester. (March 2014) - Bae, Jae-Sung; Inman, Daniel J
In the present study, a piezo-aeroelastic energy harvester using nonlinear aeroelastic behaviors is proposed, and their characteristics and performance are investigated. The energy harvester is modeled by a two-dimensional typical section airfoil. The nondimensional parameters of the harvester are introduced, and the nondimensional piezo-aeroelastic equations are formulated. For the piezo-aeroelastic analysis, the root-locus method and time-integration method are used, and the present method is verified with experimental and analytical results. The iterative method is introduced to calculate the frequency response functions of a nonlinear piezo-aeroelastic energy harvester. The aeroelastic characteristics of a linear piezo-aeroelastic energy harvester and the effects of parameters are investigated. The results show that the linear piezo-aeroelastic energy harvester can be used to generate electricity only at the vicinity of flutter speed. It is assumed that the nonlinear piezo-aeroelastic energy harvester has free play and cubic hardening in pitch. For free play, nonlinear aeroelastic results show that stable limit cycle oscillations are observed in the wide range of air speed below flutter speed when the frequency ratio is 1.3, and unstable limit cycle oscillations are observed at air speeds over flutter speed when the frequency ratio is 0.3. For cubic hardening, unstable limit cycle oscillations are observed at air speeds below flutter speed when the frequency ratio is 0.3, and stable limit cycle oscillations are observed at air speeds over flutter speed when the frequency ratio is 1.3. Finally, the authors discussed how to use these aeroelastic responses for piezo-aeroelastic energy harvesting.